A Survey on Security and Storage Issues in Internet of Things (Iot) - Mr. M. Ganesh Karthik , Dr. M.B. Mukesh Krishnan (International Journal of Advanced Science and Technology, 2020)
In broader terms, Internet of Things (IoT) can foster billions of devices, people, and services to connect and exchange information. Ubiquitous and pervasive nature of IoT systems lead to various security and storage issues. This paper reviews about threat cases and security requirements for IoT devices which extol various domains, devices, its issues and control measures. This paper also covers threat sources and classes of attacks which explain various sources of threats and types of attacks. An additional insight is provided on challenges in IoT security. This paper also explains why IoT should be integrated with cloud computing.